Analysis of Internal Audit Activity of Public Expenditure Accounting Carried Out in the National Statistical Sector: Array - Soare, Georgiana-Janina (Acta Universitatis Danubius. Œconomica, 2021)
With the help of the expense accounting specific to the national statistical sector can be quantified the efforts made towards the implementation of the strategic objectives, general and specific objectives related to the activities carried out by relevant public entities that collect, centralize, aggregate, analyze and interpret economic, financial, social information and so on. The assessment made by the internal audit on the expense accounting specific to the national statistical sector adds value to this complex activity, which is particularly important in a public entity.